Newspaper cuttings collected by Florence O'Donoghue, - O'Donoghue, Florence, 1895-1967 (1930)
Cuttings mainly relate to the history of the I.R.A. and its members, independence movements in Cork and Kerry and various commemorations. Includes two complete editions of the 'Irish Press' dated 5th September 1931 and 22nd April 1935.